Optimalisasi Biaya Operasional Penggunaan BBM Pada Kantor Induk PT PLN (Persero) Unit Induk Transmisi Jawa Bagian Tengah: Optimalisasi Biaya Operasional Penggunaan BBM - Pangastutiningtyas, Widiana Putri (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This research focuses on optimizing operational costs for using fuel oil (BBM) at PT PLN (Persero) Central Java Transmission Main Unit. In an effort to increase operational efficiency and reduce costs, this research analyzes the factors that influence fuel use. The methodology used includes analysis of historical data on fuel use. The results of the research show that there is a good cost management process so that maximum and ideal results are achieved by utilizing the cooperation of the SPBU 3440240 main office to meet maintenance profits. Thus, this research aims to enable PT PLN (Persero) to make efforts to reduce operational costs and increase the efficiency of fuel use, which is expected to have a positive impact on the company's overall financial performance.